THE APPLICATION OF THE BALANCED SCORECARD METHOD IN REVIEW FROM THE PERSPECTIVE OF EMPLOYEE SATISFACTION LEVELS AT PT. PERKEBUNAN NUSATARA III (PERSERO) KEBUN MERBAU SELATAN - Loriwan Loriwan; Sri Fajar Ayu; Adelina Lubis (SEAN Institute, 2022)
To be able to win the competition, companies need a system that can encourage performance measurement to achieve efficiency and effectiveness. The method that explicitly explains the relationship between strategy and performance measurement is the balanced scorecard. The concept of the balanced scorecard is a fairly comprehensive measure of realizing performance that can address limitations - limitations of performance measurement which previously only focused on financial aspects. The application of the balanced scorecard method to measure the performance of a company is considered capable of evaluating and improving the condition of the company and not only focusing on financial aspects but also from a non-financial perspective which also has a vital role, namely on the aspect of human resources (HR). Employees generally have their perspective on what they feel about their job and the company where they work, work culture, working environmental conditions, and the concept of giving appropriate rewards, leadership will be able to improve employee performance at work which in turn will provide satisfaction to employees. The number of samples in this study was 87 employees and the technique in data processing using the Multiple Regression method. The results showed that the variables Corporate Culture, Work Environment Facilities & Facilities, Work Environment Conditions, Reward Packages, and Leadership Style all had a positive and significant effect on satisfaction employee work at III (Persero) South Merbau Plantation and which has the greatest influence in increasing employee job satisfaction, namely the reward package, leadership style